Obowiązki i przywileje ludzi starszych według Klemensa Aleksandryjskiego - Franciszek Drączkowski (Vox Patrum, 2011)
In an old man, Clement of Alexandria sees the ideal of a perfect Christian, who thanks to intellectual and moral formation, reached the status of God’s friend. For this reason, he is entitled to the care of his family, to be honored and respected by the young people, to drink a wine and conduct conversations during the feasts and to undertake the functions of the teacher and housemaster. The old man is required to maintain a senile appearance without cosmetic procedures and to hold tactful conversations and to drink a wine in moderation during the feasts.